REFORMASI BIROKRASI, GOOD GOVERNANCE DAN ETIKA PELAYANAN PUBLIK - Janpatar Simamora (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2013)
There are so many problems overwhelming the bureaucracy, especially related to public services which is the main reason for government to reform the bureaucracy. In the process, bureaucratic reform can be said being left further than the reform on legal problems, political problems, and economic problems. Besides, the problems surrounding the bureaucratic reform are more complex and need to be handled immediately. One of the efforts from the government to support the reformation is by focusing to the improvement of the public service regulation including the regulation in favour of public servant's welfare. In order to support the good governance, the improvement of bureaucracy needs to be connected to the ethics of public servant. In doing so, we can hope that the culture and behaviour of public servant can be changed ploddingly in order to realize the success of the bureaucratic reform